2005
DOI: 10.1074/jbc.m508400200
|View full text |Cite
|
Sign up to set email alerts
|

The Glycolytic Metabolite Methylglyoxal Activates Pap1 and Sty1 Stress Responses in Schizosaccharomyces pombe

Abstract: Methylglyoxal, a toxic metabolite synthesized in vivo during glycolysis, inhibits cell growth. One of the mechanisms protecting eukaryotic cells against its toxicity is the glyoxalase system, composed of glyoxalase I and II (glo1 and glo2), which converts methylglyoxal into D-lactic acid in the presence of glutathione. Here we have shown that the two principal oxidative stress response pathways of Schizosaccharomyces pombe, Sty1 and Pap1, are involved in the response to methylglyoxal toxicity. The mitogen-acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 24 publications
3
40
0
2
Order By: Relevance
“…Yeast cells were grown in anaerobic liquid cultures in bottles filled to the top (50 ml) with YE5S until exponential phase and to the A 600 indicated for each method. We used wild-type strains 972 (h Ϫ ) and 975 (h ϩ ) (24) and AV18 (h Ϫ sty1::kanMX6) (25). To construct S. pombe strains with specific loci deleted, we transformed wild-type strain 972 with linear fragments containing ORFs fused to kanMX6 or natMX6, obtained by PCR amplification using ORF-specific primers and plasmids pFA6a-kanMX6 (26) or pFA6a-natMX6 (27) as templates, and we obtained strains NG60 (h Ϫ pfh1::natMX6) and NG40 (h Ϫ php4::kanMX6) by transforming as described previously (28).…”
Section: Methodsmentioning
confidence: 99%
“…Yeast cells were grown in anaerobic liquid cultures in bottles filled to the top (50 ml) with YE5S until exponential phase and to the A 600 indicated for each method. We used wild-type strains 972 (h Ϫ ) and 975 (h ϩ ) (24) and AV18 (h Ϫ sty1::kanMX6) (25). To construct S. pombe strains with specific loci deleted, we transformed wild-type strain 972 with linear fragments containing ORFs fused to kanMX6 or natMX6, obtained by PCR amplification using ORF-specific primers and plasmids pFA6a-kanMX6 (26) or pFA6a-natMX6 (27) as templates, and we obtained strains NG60 (h Ϫ pfh1::natMX6) and NG40 (h Ϫ php4::kanMX6) by transforming as described previously (28).…”
Section: Methodsmentioning
confidence: 99%
“…Hri1 is activated at the onset of stationary phase Phosphorylation, as well as nuclear accumulation, of Sty1 and Sty1-dependent gene expression at the transition between exponential and stationary growth was previously reported (Zuin et al, 2010;Zuin et al, 2005). We wanted to investigate the possible contribution of the eIF2a kinase pathway when the culture reached high density and reduced growth.…”
Section: Resultsmentioning
confidence: 99%
“…These findings represent what is to our knowledge the first example of Hri1 function in fission yeast. Previous reports showed that during transition to the stationary phase, Sty1 also becomes activated and triggers a transcriptional stress programme (Zuin et al, 2010;Zuin et al, 2005). Moreover, Sty1 is required for, and can be activated by different stress conditions, including hydrogen peroxide and glucose or nitrogen starvation (Vivancos et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations